Pengaruh Latihan Pasing Bawah Menggunakan Media Dinding Terhadap Peningkatan Kemampuan Pasing Bawah - Pradana, Tegar Chamim; Kusuma, Angga Indra (Jurnal Porkes, 2025)
This study aims to examine the practice of passing down using wall media to improve the ability to pass down in a bolavoli game. This study uses quantitative research with experimental methods. In this study using a matching only design where the division of the experimental group and the control group was not randomized, but used the ordinal pairing technique. The sample in this study were 30 extracurricular bolavoli participants. The implementation and data collection in this study used the test method. Based on a series of research activities that have been carried out, starting with observing the existing problems then determining the bottom pass training using wall media as a suitable exercise to improve the ability to pass down. After dividing the experimental and control groups, an initial test was carried out, namely the ability to pass down for 60 seconds, after being given an initial test, the experimental group was given treatment, namely in the form of lower pass training using wall media while the control group was not given treatment. Finally, the final test was carried out the same as the initial test. After obtaining data and calculating it can be said that lower pass training using wall media can improve lower pass skills.